Identifikasi Zona Bahaya untuk Rute Pipa Gas Bawah Laut yang Direncanakan di Pulau Pemping, Kota Batam, Kepulauan Riau - Kamajaya, Isnan Zodi; Handiani, Dian Noor (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
The installation of underwater gas pipelines in Pemping Island, Batam City, Riau Islands, requires quantitative and qualitative study, which can ensure pipeline safety. This research identifies potential hazards along the installation route using pre-lay survey data from multibeam echosounder (MBES) and side scan sonar (SSS). The interpretation of these data using Geographic Information System (GIS) software identified potential hazards: extreme slopes, sediment types, sandwave areas, and underwater cable crossings. The study results showed that 30% of the total pipeline length crosses areas with extreme slopes (15 areas), 20% crosses areas with potential sediment-type hazards (12 areas), 11% crosses sandwaves areas (1 area), and 2% has the potential to cross underwater cables (1 area). In total, about 48% (±574.13 meters) of the pipeline route crosses areas with combined potential hazards, spread across 15 areas. This information is crucial in planning appropriate protection and mitigation for pipeline installation in the region. It is expected that the findings of this study will assist pipeline installers in anticipating hazards and minimizing potential losses caused by these factors by implementing commonly used pipeline protection methods based on the identified hazards, such as trenching, buckle arrestors, and concrete weight coating.